Análisis del sistema de facturación de la Sociedad Unión Obrera Fraternidad y Progreso de la ciudad de Babahoyo - Defilippi León, Romina Verónica (2022)
Today, technology has played an important role in business success and has helped companies become more competitive in the industry and in the economy. In Babahoyo, the Sociedad Unión Obrera Fraternidad y Progreso, carries out its commercial activities through an acquired billing system, which has flaws in its functions, causing poor quality in the provision of its services. From a long time to the present, software quality assurance is an important aspect of product development. The main objectives of software quality are that it ensures acceptable levels of confidence, conformance to functional technical requirements.Due to the problems described above, this case study has the purpose of carrying out an analysis of the billing system of the Company. Analyze the billing system of the Sociedad Unión Obrera Fraternidad y Progreso of the city of Babahoyo. The methods to be used in this investigation for the reception of information was observation, whose purpose is to know the existing problems in the billing system of the institution; Taking into account the above, the ISO/IEC 25000 evaluative research will be applied as an instrument.